Implementing Environmental Management Systems in Various Organizations of Sarawak : Adoption Factors and Implementation Motivations - Ho, Lee Lee (Universiti Malaysia Sarawak (UNIMAS), 2018)
In most organizations, Environmental Management Systems (EMS) adoption is based on voluntary basis, in which the adoption depends on organization’s aspirations for better environmental performance. In Sarawak, there are only a handful of organizations that are implementing EMS. In recent years, there have been fast development envisaged in Sarawak and many resources were utilized for the various development purposes. Such development also has caused more environmental concerns in Sarawak such as pollution. Questions arise, if EMS implementation can lead to improved environmental performance, why are there only a handful of organizations in Sarawak that are adopting EMS? The primary objectives of this research are the determination of adoption factors and implementation motivations for EMS adoption in various organizations of Sarawak. The scope of this research is to conduct EMS literatures review as well as to develop a survey questionnaire with regards to EMS implementation, inviting various Sarawak organizations to reply to the survey questionnaire and thereafter, an empirical finding on the above objectives are presented. About 112 survey questionnaires invitations were forwarded to various organizations in Sarawak and a total of 47 responses were received. From this research, organizations which have implemented an EMS are mostly from larger organizations in Sarawak which have been established for more than 15 years with over 251 employees and more than one operating location. Besides, ISO 14001 is the most widely adopted EMS framework in Sarawak. As for the adoption factors investigated, EMS implementation motivation and the role of top management are the most critical factors. Management support is also another essential factor for EMS adoption among Sarawak organizations; followed by current market orientation factor. The top three implementation motivations from implementing EMS according to their importance as per v Sarawak EMS user’s organizations are (1) legal compliance; (2) improvement in operational environmental protection and (3) corporate image advantages.